Sibling mice species of the genus Sylvaemus Ognev, 1924 (Mammalia, Rodentia) in the Ukrainian Carpathians - Barkaszi, Zoltán (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
Three species of the genus Sylvaemus occur in the region of the Ukrainian Carpathians: the yellow-necked field mouse (S. tauricus), the long-tailed field mouse (S. sylvaticus) and the pygmy field mouse (S. uralensis). Issues of the genus’s taxonomy and identification of species have remained controversial in some parts of the geographic range, while in the Ukrainian Carpathians they have been studied scarcely at all. We studied about 250 mice specimens from the Ukrainian Carpathians belonging to the genus Sylvaemus, among which 216 were analysed morphometrically based on 4 external and 11 cranial characters. Results indicate that by linear body dimension only S. uralensis can be differentiated with high probability. For the pair of species tauricus–sylvaticus, the hind foot length is the least variable among linear body characters, which might be considered diagnostic, although values of this character also tend to overlap. To identify species correctly, it is necessary to use craniometrical characters. For the pair of tauricus–sylvaticus, the least variable among the 11 studied characters are the upper molars length (M13), braincase width (CRB), and braincase height (CRH). Mixed samples of adult specimens of the three species can be differentiated with minimal or practically no overlap by using the relation of the upper molars length to braincase width, condylobasal length, and auditory bulla length. Analysis of characters’ uniformity in adult specimens showed that S. tauricus and S. sylvaticus differ from one another the most by the upper molars length (M13), braincase width (CRB), braincase height (CRH), condylobasal length (CBL), and auditory bulla length (BUL). A similar tendency was revealed for the pair of S. sylvaticus and S. uralensis. A regional identification key was developed for differentiation of adult mice, which allows identifying reliably 93.5% of specimens. Results of the revision of samples suggest that S. tauricus has the widest altitudinal and habitat preferences, S. sylvaticus occurs mainly in humid floodplain biotopes (shrubs, woods) entering far into the mountains along river valleys, while S. uralensis is represented only by few records from lowland floodplain habitats.